A Ghost from the Past. (October 2016) - Chapman, H.R.
This narrative illustrates how childhood trauma can influence the ability to cope with dental fear and treatment. It also demonstrates that a sympathetic dentist with the appropriate training can help these patients to overcome their dental fear and give them the skills to deal with other problems.